Preparation Of Simple Financial Statements For MSME Using Microsoft Excel Accounting Application: A Case Study On The Mawar Ikat Weaving Group In Tawiri Negeri - Hasmawati Hasmawati; Chrestiana Aponno; Septina Louisa Siahaya; Rendy Usmany (Pusat Riset dan Inovasi Nasional, 2023)
The Mawar Ikat Weaving Group in Tawiri village or negeri has not been able to record accounting or prepare financial reports in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (FAS MSMEs). This business has not implemented an automated accounting recording system yet and only uses paper. Besides, there is no human resources who understand accounting. Therefore, there is no financial reports according to FAS MSMEs. Financial reports are also recommended to be presented computerised, for example by using Microsoft Excel. Financial reports from Excel were chosen because they are neat, easy to read and understand, automatically calculated accurately, practical when there are changes, and cost-effective.The application of this standard is expected to help and facilitate the Mawar Ikat weaving business in preparing financial reports.This research is a type of action research aiming to improve the quality of a situation or problem by carrying out actions or interventions systematically planned and tested. Recording company transactions into journals and preparing financial reports involve several stages of the accounting process, namely Designing the List of Accounts, Recording Transactions in the Journal Posting to the Ledger, Preparation of the Balance Sheet, and Preparation of Financial Statements. The preparation of simple financial statements using the excel accounting application is a positive step for MSME players. Despite limited resources, a basic understanding of accounting and the ability to prepare financial statements will help MSMEs maintain the sustainability of their business and fulfil internal and external financial information needs.